Mining Urban Data (Part C). (March 2017) - Andrienko, Gennady; Gunopulos, Dimitrios; Ioannidis, Yannis; Kalogeraki, Vana; Katakis, Ioannis; Morik, Katharina; Verscheure, Olivier
Abstract: Modern cities generate a flood of rich and varied data. New information sources like public transport and wearable devices provide opportunities for novel applications that will improve citizens׳ quality of life by reducing transportation time, enhancing city planning, and improving air quality to name a few applications. From a data science perspective, data emerging from smart cities give rise to a lot of challenges that constitute a new interdisciplinary field of research. This article introduces the third part of a special issue on the topic 'Mining Urban Data' published in the journal Information Systems.